Molecular characteristic of Staphylococcus aureus isolated from patients with nasal carriage infections - A. A. Hammoudi; N. S. Mohammed (Regulatory Mechanisms in Biosystems, 2025)
Staphylococcus aureus is a path o genic microorganism that lead s to a range of infections in both humans and animals due to its ability to form bi o films an d develop antibiotic resistance. A total of 150 nasal swabs were co l lected from outpatients, from which 52 (34.7%) isolates were identified as S. aureus . Identification of S. aureus isolates was conducted by biochemical analysis ( catalase and coagulase a s says). Biofilm formati on was evaluated using Congo -red agar , and the presence of icaA and icaD genes was confirmed through molecular analysis. Antibiotic sensitivity patterns were assessed by regular antimicrobial testing. All the samples were catalase- and coagulase-positive. Biofilm production was d e tected in 15 (28.8%) specimens. All the samples were icaA and icaD gene- positive. Antibiotic resistance tests confirmed that the highest resistance was exerted against Oxacillin (86.5%), Tetracycline (67.3%), Ciprofloxacin (65.4%), and Erythromycin (63.5%). Vancomycin and Gentamicin demo n strated a strong efficacy. A m oderate efficacy was achieved with Rifampin (96.2%), Cotrimoxazole (94.2%), and Augmentin (90.4%). The present study highlighted the rate of antibiotic resi s tance among nasal S. aureus isolates, including resistance to Oxacillin, which is the gold standard for methicillin-resistant S. aureus (MRSA). These outcomes were further elucidated by positive biofilm genes ( icaA and icaD ), suggesting the pathogenic potential of these isolates. T hese outcomes warrant further study, and effective antibiotic criteria are essential to manage the increasing resistance of S. aureus to ensure the effectiveness of avail a ble therapy.